Gerakan 3M Plus dengan Pendekatan Surveilans Entomologi dalam Pencegahan DBD di Dusun Olat Rarang Desa Labuhan Sumbawa - Abdul Hamid; Hamdin Hamdin (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in endemic areas, including Olat Rarang Hamlet, Labuhan Sumbawa Village. Effective dengue prevention requires active community involvement supported by entomological surveillance data. This community service activity aimed to enhance community awareness and participation in dengue prevention through the implementation of the 3M Plus Movement integrated with an entomological surveillance approach using the House Index (HI), Container Index (CI), and Breteau Index (BI) indicators. The activity was conducted on December 6, 2025, involving local community members and public health students. The methods included health education, larval surveys in houses and water-holding containers, and community-based mosquito breeding site eradication. The results indicated that houses and containers positive for Aedes larvae were still present, reflecting a moderate risk of dengue transmission. However, the implementation of the 3M Plus Movement improved community knowledge, awareness, and participation in vector control. Integrating the 3M Plus Movement with entomological surveillance is an effective promotive and preventive strategy based on community empowerment for sustainable dengue prevention.